Pelaksanaan Clinical Decision Support System Pada Rekam Medis Elektronik di Klinik Pendidikan UPT Poliklinik Politeknik Negeri Jember: Literature Review - Yuli Qodariyah; Lay Arif Firiandri Yulius; Sheila Stefani; Vidia Andita Sari; Novita Rahayu; Vip Paramarta (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The introduction of Electronic Medical Records (EMR) along with Clinical Decision Support Systems (CDSS) has brought about significant changes in healthcare services. This research focuses on the implementation of EMR and CDSS in an educational clinic in Jember Regency, Indonesia. The implementation method used is